KAJIAN PROSPEK BATU PERMATA BANJARBARU DALAM PERSPEKSTIF GEOLOGI BAHAN GALIAN - Adip Mustofa (INFO-TEKNIK, 2005)
Banjarbaru has a very complex and interesting geologic condition.  The stratigraphy in this area has a unique and complex characteristic, with Pre-Tertiary until Quarterly in age.  The oldest type of rock found has a Yura-age, consists of: Ultra-mafic rock (Mub) and Metamorphic rock (Mm). Both of these rock-types outspread unconformity under a Pre-Tertiary lithological units (Kapur), likes Keramaian Formation (Kak), sedimentary of volcaniclastic Pitanak Formation (Kvpi). These Pre-Tertiary rocks laid unconformity under a group of Tertiary and Quarterly age of lithology, consists of: Tanjung Formation (Tet), Berai Formation (Tomb), Dahor Formation (TQd) and alluvium sedimentation (Qa).Gemstone deposit, included in its type and occurrences, conducted by long geological processes.  As known, the Regional Geology of Kalimantan, especially inSouth Kalimantanregion, has proceeded in age of Pre-tertiary until Quarter.  This process supported the forming of gemstones and its accumulation.  Kinds of gemstones and semi-gemstones probably accumulated by this geology process which consists of: primary diamond, tourmaline, blue-sapphire, Jade, Garnet, Secondary diamond, Quartz, Zircon, Spinel, opal, etc. Nowadays, the real potency of gemstone and semi-gemstone has not been known yet, so an effort of follow-up exploration is needed.